Characterization of urban water use and water demand forecasting using the Integrated Urban Water Model in Sao Paulo, Brazil - Batista, Giovana, author; Arabi, Mazdak, author; Sharvelle, Sybil, author; Dozier, Andre, author (Colorado State University. Libraries, 2017)
Urban sprawl over the past decades have put water resources under pressure in urban areas due to constantly increasing demand and impaired quality. Particularly in developing countries, investments in this sector are still scarce. The application of the Integrated Urban Water Model - IUWM - for the characterization of current and future urban water demand in the municipality of Sao Paulo, Brazil, is pioneering in applying the model outside of the United States. The model also evaluates water conservation scenarios, cost saving options and can be of use for water utilities and urban planners.
028 - Giovana Batista
Urban water demand characterization in Sao Paulo, Brazil, using IUWM
Keywords: urban water; IUWM; Sao Paulo; water conservation